2002
DOI: 10.1021/ma0114180
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Enhanced Crystallization in Isotactic Polypropylene. 3. Evidence for a Kinetic Pathway to Nucleation

Abstract: The exact value of the wall shear strain is not known. The known quantities are the wall shear stress, the duration for which it is applied and the mass extruded during that time. The flow curve of the polymer at a temperature above the nominal melting temperature is also known, and the time-temperature shift behavior of polypropylene can be applied to the melt. Some of the unknowns that prevent quantitative determination of the wall shear strain are the transient behavior upon inception of non-linear shearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
197
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(204 citation statements)
references
References 40 publications
7
197
0
Order By: Relevance
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
See 2 more Smart Citations
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
“…1,[59][60][61][62][63] Under flow, there are substantial evidences of the formation of long-lived metastable oriented structures, even at temperatures above the normal melting point of the polymer (T mp ). 44,52,[64][65][66][67][68][69][70][71][72][73] The first direct experimental evidence was obtained from rheoRaman 66 studies of polyethylene (PE) melt at 140 8C, a temperature significantly above its melting point. It was shown that a fraction of PE molecules adopted all-trans sequence configurations upon shearing, which remained stable for several hours even after cessation of shear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The route to crystallization during flow is generally accepted to be via the formation of 'shishkebab' morphology [6][7][8][9]. Proposed mechanisms and kinetics for the formation of shish-kebab morphology usually relate to data from shear flow conditions using custom made shearing devices [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, the amount of mechanical work performed by flow on the polymer melt controls the formation of oriented shish nuclei via the shear-induced nucleation of stretched molecules. In this respect, it needs to be pointed out that neither a critical stress 15 nor a critical strain 16 should be used to describe the onset of oriented crystal morphology as these parameters relate to the later stage-transformation of shish nuclei rows into a fibrillar structure (shish). In this study, boundary specific work, involving both the shear rate and the time of shearing, is used as a term to describe the threshold flow conditions for the onset of an oriented morphology.…”
mentioning
confidence: 99%